2022
DOI: 10.1002/ijc.34333
|View full text |Cite
|
Sign up to set email alerts
|

The current status of cell‐free human papillomavirus DNA as a biomarker in cervical cancer and other HPV‐associated tumors: A review

Abstract: Tumor cells release fragments of their DNA into the circulation, so called cell-free tumor DNA (ctDNA), allowing for analysis of tumor DNA in a simple blood test, that is, liquid biopsy. Cervical cancer is one of the most common malignancies among women worldwide and high-risk human papillomavirus (HR-HPV) is the cause of the majority of cases. HR-HPV integrates into the host genome and is often present in multiple copies per cell and should thus also be released as ctDNA. Such ctHPV DNA is therefore a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…This is a prospective, safety and feasibility trial that will include a total of 30 subjects according to the relevant study [18,19] and will not be subject to formal sample size measurement.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This is a prospective, safety and feasibility trial that will include a total of 30 subjects according to the relevant study [18,19] and will not be subject to formal sample size measurement.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…With the rapid development of liquid biopsy technology, HPV-ctDNA-based assessment of MRD status (hereinafter referred to as HPV/MRD) can become an ideal biomarker for the treatment and prognosis of malignant tumors. The feasibility of detecting ctHPV DNA in the plasma of cervical cancer patients has been a rmed by Prof. Sivars L's team in Gynecologic Oncology and the International Journal of Cancer [18,19], although optimized protocols and ultra-sensitive techniques are needed to obtain su cient sensitivity, ctHPV DNA is a potential prognostic biomarker for cervical cancer patients. A prospective study by Sivars et al [20] similarly concluded that follow-up plasma ctHPV DNA is a promising prognostic biomarker for LACC patients and that monitoring of plasma ctHPV DNA concentrations in patients with follow-up can help analyze their response to treatment and early detection of LACC recurrence.…”
mentioning
confidence: 99%
“…Among these CC is primarily caused by persistent human papillomavirus (HPV) infection, with HPV types 16 and 18 responsible for 71% of cases worldwide ( Choi et al, 2023 ; Reich and Regauer, 2023 ). Prevention and treatment of high-risk HPV cervical infections remain the main approach in combating CC, with the introduction of CC vaccines being a major development in recent years, together with screening technologies ( Rahangdale et al, 2022 ; Rimel et al, 2022 ; Sivars et al, 2022 ; Sun et al, 2022 ; Sabeena, 2023 ). OC, as the seventh most commonly diagnosed female cancer worldwide, poses as the fifth leading cause of cancer-related deaths in women and the most lethal of all gynecological malignancies ( Chen et al, 2023 ; Ye et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers could be used in early cancer detection, in the follow-up of detected diseases, and in the evaluation of responses and resistance to therapy [ 12 ]. These biomarkers have the advantage of being relatively non-invasive for patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%